URBANIZATION, GLOBALIZATION AND SOCIAL EXCLUSION: REFLECTIONS FROM BRAZILIAN CASE - Nascimento, Ederson (Revista Geográfica de América Central., 2016)
This paper presents a historical and geographical analysis of the evolution of the urbanization process in Brazil, focusing on its relations with globalization and the characteristics of the main processes of social exclusion initiated during this process. The urbanization is understood from the influences of the global economy, by the action of transnational corporations and the State, in the acceleration of industrialization and of modernization of agriculture in the country, which fueled the rural exodus and the territorial redistribution of the population. The correlation between technological innovations in productive sectors and the easing/casualization of labor market, maintenance of old social structures and the fragility of public policies to promote citizenship, worsened the scenario of inequality and social exclusion, with its concentration in urban centers. It emphasizes the importance of government action to promote policies that can reduce or even reverse the exclusion of membership in the country.